Women's Law and Grassroots Justice in Uganda - Wengi, Okumu; Wengi, Okumu (LawAfrica Publishing Ltd, 2011)
This posthumous publication is a collection of essays some of which are based on the author?s research work while others record her thoughts on issues she regarded as important. The materials, which were written between 1991 and 1996, cover a range of subjects that have been tied together under the theme of women, law and justice in Uganda. They represent the author?s central concerns, interests and views as they developed over the years.